TEACHING SPIRITUAL-EDUCATIONAL AND MYSTICAL WORDS UNDER ALISHER NAVOI'S "NASAYIM UL-MUHABBAT" USING INTERACTIVE METHODS (Academia Science Repository, 2023)
In this article, the lexicon of Persion-tajik words,Arabic words used in the meanings specific to the old Uzbek literary language in Alisher Navoi‘s “Nasoyim ul-muhabbat” were determined. The scope of application of paremiological units was studied consistently in terms of quantity in terms of quantity and content.